The Relationship Between Teachers’ Self-Efficacy Perceptions and Self-Esteem Levels - Canaslan, Ayten; Sönmez, Azmi; Cemaloğlu, Necati (Technium Social Sciences Journal, 2025)
The purpose of this study is to determine the relationship between teachers’ perceptions of interpersonal self-efficacy and their self-esteem levels. In the study, the relational survey method, which is included in the general survey model based on quantitative data, was used. The population of the study consists of 4979 teachers working in public schools in Kastamonu province of Turkey in the 2024-2025 academic year, and the sample consists of 230 teachers selected by simple random sampling method. Interpersonal Self-Efficacy Scale and Self-Esteem Scale were used as data collection tools in the study. SPSS 25 statistical package program was used to analyze the data. In the analysis of the first two sub-problems, arithmetic mean and standard deviation analyses were performed for descriptive statistics. Correlation analysis was used to analyze the third sub-problem and regression analysis was used to analyze the fourth sub-problem. According to the results of the research, teachers’ perception of self-efficacy is at a very high level. When the sub-dimensions were analyzed, it was seen that the perception of self-efficacy related to obtaining support from colleagues was higher than the perception of self-efficacy related to obtaining support from administrators and perceived self-efficacy in classroom management. Teachers’ self-esteem is at a high level. As a result of the research, it was seen that there was a moderate positive significant relationship between teachers’ self-efficacy perceptions and their self-esteem. As teachers’ perceptions of perceived self-efficacy in classroom management, perceptions of perceived self-efficacy in obtaining support from colleagues and perceptions of perceived self-efficacy in obtaining support from administrators increase, their self-esteem increases. Among the sub-dimensions of self-efficacy, teachers’ perceptions of perceived self-efficacy in classroom management and perceptions of perceived self-efficacy in obtaining support from colleagues are significant predictors of teachers’ self-esteem. All findings were discussed in relation to the related literature.